Exploring the Relationship between Chronotype and Waist Circumference: A Scoping Review - Barve, Samir Sumant; Joshi, Sonopant Ganapatrao; Duraphe, Prashant Sharad (Sleep Science, 2025)
Understanding the relationship between chronotype and waist circumference (WC) has implications for metabolic health management. The present article overviews the available literature, the knowledge gaps, and the insights for future research. We conducted a search on the Scopus, Web of Science, and PubMed electronic databases and followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) extension for scoping reviews. A total of 33 articles were included in the review. The studies primarily identified that people with the evening chronotype presented a higher mean WC compared to those with the morning chronotype. However, the difference was not significant in all studies. A significant positive correlation of the WC with chronotype scores denoting eveningness was found in 88% of the studies. The cut-off values on the scales to categorize subjects into different chronotypes may need to be defined for communities living across the globe. We conclude that higher WC values are associated with eveningness. However, this finding should be validated using objective measures of chronotype assessment.
Keywords: chronotype; obesity; abdominal; waist circumference